2015
DOI: 10.1098/rspb.2015.0602
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of parasitism: costs of infection to other individuals can be greater than direct costs borne by the host

Abstract: Parasitic infection has a direct physiological cost to hosts but may also alter how hosts interact with other individuals in their environment. Such indirect effects may alter both host fitness and the fitness of other individuals in the host's social network, yet the relative impact of direct and indirect effects of infection are rarely quantified. During reproduction, a host's social environment includes family members who may be in conflict over resource allocation. In such situations, infection may alter h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
12
3
Order By: Relevance
“…Previous studies have found chick sex, hatch date and 357 rank to be important in determining responses to anti-parasite treatment (Reed et al 2008(Reed et al , 2012 358 Granroth-Wilding et al 2014, 2015), yet we found no strong evidence that worm burden varied 359 with any of these host traits. This suggests that differences in response may arise due to variation in 360 tolerance between the subclasses of juvenile as opposed to differences in burden.…”
Section: Effect Of Infection On Host Performance 340contrasting
confidence: 60%
See 4 more Smart Citations
“…Previous studies have found chick sex, hatch date and 357 rank to be important in determining responses to anti-parasite treatment (Reed et al 2008(Reed et al , 2012 358 Granroth-Wilding et al 2014, 2015), yet we found no strong evidence that worm burden varied 359 with any of these host traits. This suggests that differences in response may arise due to variation in 360 tolerance between the subclasses of juvenile as opposed to differences in burden.…”
Section: Effect Of Infection On Host Performance 340contrasting
confidence: 60%
“…Several studies of parasitism in the shag have used anti-helminthic treatment as an 562 experimental approach to investigate the effects of nematode infection (Reed et al 2008(Reed et al , 2012 563 Burthe et al 2013;Granroth-Wilding et al 2014, 2015. The injectable, broad-spectrum 564 antihelminthic drug, Ivermectin (Panomec©, Merial UK) has thus been shown to affect chick 565 survival and growth, adult condition, and behaviour of both adults and chicks, strongly suggesting 566 that treatment affects worm burden.…”
Section: Cunningham Eja and Daunt F (2013) Endoscopy As A Novmentioning
confidence: 99%
See 3 more Smart Citations